Sensitivity of caterpillars of the pine tree lappet moth Dendrolimus pini to native isolates of entomopathogenic nematodes. Issue 4 (2nd October 2019) - Tumialis, Dorota; Skrzecz, Iwona; Mazurkiewicz, Anna; Pezowicz, Elżbieta
Abstract: The pine tree lappet moth Dendrolimus pini (Lasiocampidae) is one of the most dangerous pests of pine Pinus sylvestris stands in Central Europe. To develop biological control method of this pest, the bioassay was made to assess the sensitivity of D. pini caterpillars to native EPMs strains representing two species: Steinernema feltiae and Heterorhabditis megidis in laboratory conditions. The results showed higher activity of S. feltiae strains which parasitized 86.7 - 100% of D. pini caterpillars, compared to the 20-100% of insects parasitized by H. megidis strain. Most nematodes were found in caterpillars treated with S. feltiae (in average 40 IJs/caterpillar), the least – in individuals parasitized by H. megidis (in average IJs/caterpillar). No effect of dose and temperature on parasitizm was found with S. feltiae strains while in H. megidis increased doses resulted in higher extensity of parasitism. The results indicate higher biological activity of S. feltiae strains and advisability of their further studies in field experiments.